Separator and lithium secondary battery comprising the same

KR103022185B1Active Publication Date: 2026-09-18LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020240164623
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-11-24
Filing Date
2024-11-18
Publication Date
2026-09-18
Estimated Expiration
2044-11-18
Patent Text Reader

Abstract

The present invention relates to a separation membrane comprising: a substrate layer; and a porous coating layer located on one or both sides of the substrate layer and comprising a first inorganic particle, a second inorganic particle, and an acrylic binder, wherein the ratio of the average particle size (D50) of the second inorganic particle to the average particle size (D50) of the first inorganic particle is 1.4 to 2.0, the content of the first inorganic particle is greater than the content of the second inorganic particle based on the total weight of the porous coating layer, and the thickness of the porous coating layer is 1.2 μm to 2.0 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a separator and a lithium secondary battery including the same, and specifically, to an inorganic material of bimodal distribution with a specific average particle size (D 50 The present invention relates to a separator having improved wet shrinkage and dry shrinkage by including a porous coating layer mixed in a ratio and a specific weight ratio, wherein the porous coating layer has a thickness of 1.2 μm to 2.0 μm, and a lithium secondary battery including the same. Background Technology

[0003] With the increasing technological development and demand for mobile devices, the demand for secondary batteries as an energy source is rapidly rising. Among these secondary batteries, lithium-ion batteries, which possess high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.

[0004] Generally, lithium secondary batteries are manufactured using a negative electrode, a positive electrode, a separator interposed between them, and an electrolyte that serves as a medium for transferring lithium ions.

[0005] Among these, the separator is an inert material that does not participate in electrochemical reactions, but it provides a pathway for lithium ions to move to operate the battery and acts as a material that separates the physical contact between the anode and cathode; as such, it is one of the key materials that significantly affects the performance and stability of the battery.

[0006] Meanwhile, lithium-ion batteries can easily generate heat due to the kinetic energy produced during repeated charging and discharging cycles, and separators are vulnerable to this heat. In particular, separators using polyethylene (PE) may begin to melt around 130°C, leading to a 'shutdown' phenomenon where pores close; above 150°C, they may completely melt, failing to prevent internal short circuits and potentially collapsing. To overcome these problems, research on separators with enhanced durability by coating the surface with inorganic particles has recently been ongoing.

[0007] However, separators developed to date have not had sufficient durability. For example, when a cylindrical cell with a conventional separator was disassembled after a hot box evaluation at 130°C, the free-standing separator located in the cell core contracted excessively in the TD direction, causing the electrode portion to be exposed.

[0008] Meanwhile, since the separator in a lithium secondary battery is used in a state impregnated with the electrolyte, the rate of dimensional change of the separator in the wet state is more significant than in the dry state.

[0009] Therefore, there is a need to develop a separator capable of ensuring high-temperature dimensional stability of a wet state separator in a high-temperature electrolyte environment. The problem to be solved

[0011] The present invention aims to solve the above-mentioned problems by providing a separator capable of suppressing shrinkage even when impregnated in a high-temperature electrolyte, and a lithium secondary battery including the same. means of solving the problem

[0013] [1] The present invention comprises a substrate layer and a porous coating layer located on one or both sides of the substrate layer, the coating layer comprising a first inorganic particle, a second inorganic particle, and an acrylic binder, wherein the average particle size (D) of the first inorganic particle50 The average particle size (D) of the second inorganic particle mentioned above for ) 50 A separation membrane is provided in which the ratio of ) is 1.4 to 2.0, the content of the first inorganic particle is greater than the content of the second inorganic particle based on the total weight of the porous coating layer, and the thickness of the porous coating layer is 1.2㎛ to 2.0㎛.

[0014] [2] The present invention, in [1] above, has an average particle size (D) of the first inorganic particle. 50 ) provides a separation membrane having a thickness of 0.32㎛ to 0.5㎛.

[0015] [3] The present invention, in [1] or [2], wherein the average particle size (D) of the second inorganic particle is 50 ) provides a separation membrane having a thickness of 0.45㎛ to 0.70㎛.

[0016] [4] The present invention provides a separation membrane in which, in any one of [1] to [3], the porous coating layer comprises the first inorganic particle:the second inorganic particle in a weight ratio of 55:45 to 95:5.

[0017] [5] The present invention provides a separation membrane in which, in any one of [1] to [4], the first inorganic particle and the second inorganic particle each independently comprise one or more selected from the group consisting of aluminum oxide (Al2O3), boehmite (AlOOH), silicon dioxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2) and zeolite.

[0018] [6] The present invention provides a separation membrane in which, in any one of [1] to [5], the porous coating layer has a porosity of 60% or less.

[0019] [7] In any one of [1] to [6], the present invention has a loading amount of the porous coating layer of 4.9 g / cm² 2 Up to 7.0 g / cm²2 It provides a separation membrane that is.

[0020] [8] The present invention, in any one of [1] to [7], wherein the packing density of the porous coating layer is 1.4 g / cm³ 3 Up to 2.0 g / cm² 3 It provides a separation membrane that is.

[0021] [9] The present invention provides a separation membrane in which, in any one of [1] to [8], the porous coating layer is formed by applying a slurry composition having a solid content of 20% to 50% by weight to one or both sides of the substrate layer.

[0022]

[10] The present invention provides a separation membrane in which, in any one of [1] to [9], the thickness of the separation membrane is 11 μm to 14 μm.

[0023]

[11] The present invention provides a separator in which, in any one of [1] to

[10] , the MD shrinkage rate is 0.5% to 7.0% and the TD shrinkage rate is 0.5% to 5.5% when the separator is impregnated with an electrolyte and then left at 130°C for 30 minutes.

[0024]

[12] The present invention provides a separator in which, in any one of [1] to

[11] , the MD shrinkage rate is 1% to 50% and the TD shrinkage rate is 2% to 40% when the separator is left at 150°C for 30 minutes.

[0025]

[13] The present invention provides a lithium secondary battery comprising a separator according to any one of [1] to

[12] . Effects of the invention

[0027] The separation membrane according to the present invention has a specific average particle size (D 50By using a porous coating layer having a thickness of 1.2㎛ to 2.0㎛ containing first inorganic particles and second inorganic particles satisfying the ratio and weight ratio, the shrinkage of the separator is suppressed in a high-temperature electrolyte. Accordingly, when using the separator of the present invention, it has high heat resistance characteristics due to high dimensional stability compared to conventional separators, so it is possible to isolate the anode and cathode in a high-temperature electrolyte and prevent internal short circuits.

[0028] The effects according to the present invention are not limited to those exemplified above, and various other effects are included in this specification. Specific details for implementing the invention

[0030] The present invention will be described in detail below.

[0031] Terms and words used in this specification and claims shall not be interpreted as being limited to their ordinary or dictionary meanings, but shall be interpreted in a meaning and concept consistent with the technical spirit of the invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention.

[0032] The terms used herein are for describing the embodiments and are not intended to limit the invention. In this specification, the singular form includes the plural form unless specifically stated otherwise in the text. As used herein, "comprises" and / or "comprising" do not exclude the presence or addition of one or more other components in addition to the components mentioned.

[0033] In the present invention, the average particle size (D 50 ) refers to the particle size at the 50% reference of the volume-cumulative particle size distribution of the powder to be measured, such as inorganic particles. The above average particle size (D 50) can be measured using the laser diffraction method. For example, the powder to be measured can be dispersed in a dispersion medium, then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), irradiated with ultrasound of about 28 kHz at an output of 60 W, obtained a volume cumulative particle size distribution graph, and then measured by determining the particle size corresponding to 50% of the volume cumulative amount.

[0034] In the present invention, the porosity can be calculated from the ratio of the packing density of the porous coating layer to the packing density of the non-porous coating. The non-porous coating packing density can be calculated by applying the bulk density of the raw material used and the coating composition, assuming a porosity of 0%.

[0035] In the present invention, the loading amount of the porous coating layer (R, unit: g / cm²) 2 ) can be measured by measuring the average weights W1 and W2 of each of the coated separator and base film cut into 5cm x 5cm pieces and measuring them 6 times each, and then substituting them into Equation 1 below.

[0036] [Equation 1]

[0037] R = (W1-W2) / 25

[0038] In the present invention, the packing density (D, unit: g / cm²) of the porous coating layer 3 ) is the loading amount (R) of the porous coating layer and the total thickness (T) of the separator. total ) and the thickness of the substrate layer of the separator (T c It can be calculated by substituting ) into Equation 2 below.

[0039] [Equation 2]

[0040] D = R / {(T total - T c ) × 0.0001}

[0041] In the present invention, the MD direction (Machine Direction) refers to the length direction of the membrane, and the TD direction (Transverse Direction) refers to the width direction of the membrane.

[0042] In the present invention, the wet shrinkage is a value obtained by cutting a separator into a size of 5 cm × 5 cm, placing it in a 10 cm × 9 cm pouch together with an electrolyte, impregnating it, storing it in a 130°C convection oven for 30 minutes, and then separating the separator from the pouch and measuring the shrinkage rate in the MD direction and TD direction.

[0043] In the present invention, the dry shrinkage is a value obtained by measuring the shrinkage rate in the MD direction and the TD direction after removing a separator cut to a size of 5 cm × 5 cm and storing it in a 150°C convection oven for 30 minutes.

[0045] Separator

[0046] First, the separation membrane according to the present invention will be described.

[0047] The separation membrane according to the present invention comprises a substrate layer and a porous coating layer located on one or both sides of the substrate layer, the coating layer comprising a first inorganic particle, a second inorganic particle, and an acrylic binder.

[0048] In the present invention, the substrate layer is a thin film of an insulating material intended to allow only lithium ions to pass through and prevent short circuits, and may be a porous polymer film, for example, a polymer film formed from any one polymer selected from the group consisting of polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyetheretherketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene oxide, cyclic olefin copolymer, polyphenylene sulfide, polyethylene naphthalate, Teflon, and polytetrafluoroethylene, or a copolymer or mixture of two or more of these.

[0049] Preferably, the substrate layer may be a polyolefin-based substrate comprising a polyolefin. The polyolefin-based substrate has excellent shutdown capabilities and can contribute to improving the safety of the battery. The polyolefin-based substrate may be selected from, for example, a polyethylene single membrane, a polypropylene single membrane, a polyethylene / polypropylene double membrane, a polypropylene / polyethylene / polypropylene triple membrane, and a polyethylene / polypropylene / polyethylene triple membrane. Additionally, the polyolefin-based resin may include a non-olefin resin in addition to the olefin resin, or may include a copolymer of an olefin and a non-olefin monomer.

[0050] The substrate layer may have a thickness of about 1 μm to 20 μm, preferably 1 μm to 15 μm, and more preferably 1 μm to 10 μm. When the thickness of the substrate layer satisfies the above range, it is desirable in that it has good air permeability, can have mechanical tensile strength capable of meandering during the cell assembly process, has strong puncture strength that is not penetrated by dendrite-shaped lithium precipitates formed on the surface of the negative electrode during overcharging, and is advantageous for increasing the output and capacity of the battery.

[0051] The porous coating layer is located on one or both sides of the substrate layer to improve the mechanical strength and heat resistance of the substrate layer, and the porous coating layer according to the present invention has an average particle size (D 50 ) includes different first inorganic particles and second inorganic particles, and an acrylic binder.

[0052] Average particle size (D 50 When two types of inorganic particles with different values ​​are included in the porous coating layer, the average particle size (D 50 Average particle size (D) among large particles 50 Since small particles are arranged, the ratio of voids existing between inorganic particles is reduced, which increases the packing density of the porous coating layer and provides the effect of increased thermal stability. However, the average particle size (D 50 Even when using two types of inorganic particles with different values, the average particle size (D) between the inorganic particles 50 If the difference is too large, the pore size or porosity within the porous coating layer becomes too small, leading to reduced electrolyte impregnation, which may result in a degradation of electrochemical properties, and the average particle size (D) between inorganic particles 50 If the difference is too small, the effect of improving thermal stability is negligible.

[0053] Accordingly, in the present invention, the average particle size (D) of the first inorganic particle and the second inorganic particle 50 By ensuring that the ratio satisfies a specific range, the thermal shrinkage rate of the separator can be reduced while minimizing the degradation of electrochemical properties.

[0054] Specifically, in the present invention, the average particle size (D) of the first inorganic particle 50 The average particle size (D) of the second inorganic particle mentioned above for ) 50 The ratio of ) can be 1.4 to 2.0, preferably 1.4 to 1.8, and more preferably 1.4 to 1.5.

[0055] The average particle size (D) of the first inorganic particle mentioned above50 The average particle size (D) of the second inorganic particle mentioned above for ) 50 If the ratio of ) exceeds 2.0, there is a problem in that the wet shrinkage and dry shrinkage increase due to excessively large pores, thereby increasing the probability of an internal short circuit in the battery, and the average particle size (D) of the first inorganic particle is 50 The average particle size (D) of the second inorganic particle mentioned above for ) 50 If the ratio of ) is less than 1.4, there is a problem where the dispersibility of inorganic particles decreases or particles are distributed within already formed pores, resulting in low air permeability.

[0056] In contrast, the average particle size (D) of the first inorganic particle and the second inorganic particle mentioned above 50 When the ratio of ) satisfies the scope of the present invention, the first inorganic particles with a small particle size may be included between the second inorganic particles with a large particle size, and accordingly, the ratio of voids existing between inorganic particles is reduced. As a result, the packing density of the porous coating layer is increased, so shrinkage due to heat is reduced when left at room temperature and high temperature, thereby increasing the high-temperature stability of the battery. That is, the average particle size (D) of the first inorganic particles described above 50 The average particle size (D) of the second inorganic particle mentioned above for ) 50 When the ratio of ) is set to 1.4 to 2.0, preferably 1.4 to 1.8, and more preferably 1.4 to 1.5, the bonding strength of the separator to the substrate, as well as heat resistance and moisture resistance, can be improved, and accordingly, the safety and lifespan characteristics of the battery can be improved.

[0057] In the present invention, the average particle size (D) of the first inorganic particle 50 ) may be 0.32㎛ to 0.5㎛, preferably 0.32㎛ to 0.45㎛, more preferably 0.32㎛ to 0.4㎛. The average particle size (D) of the first inorganic particle is 50If ) is less than 0.32㎛, it is difficult to form a porous shape within the coating layer, resulting in a problem of reduced ion conductivity; furthermore, as the surface area relatively increases and the contact area with the binder widens, there is a problem of excessive binder consumption causing the coating layer to become thicker; and there is a problem of reduced dispersibility due to aggregation among the first inorganic particles. In addition, the average particle size (D) of the first inorganic particles 50 If ) exceeds 0.5㎛, there is a problem in that the electrolyte is not uniformly distributed due to the formation of non-uniform pores during the porous structure formation process. The average particle size (D) of the first inorganic particle is 50 When the above range is satisfied, the thermal stability improvement effect may occur because the optimal size ratio in terms of packing density with the second inorganic particle is satisfied.

[0058] In addition, the average particle size (D) of the second inorganic particle mentioned above 50 ) may be 0.45㎛ to 0.70㎛, preferably 0.45㎛ to 0.60㎛, more preferably 0.48㎛ to 0.55㎛. The average particle size (D) of the second inorganic particle is 50 If ) is less than 0.45㎛, the cohesive force between particles becomes strong, resulting in an uneven distribution of particles within the porous coating layer; and when the electrolyte penetrates into the porous coating layer, the degree of expansion of the porous coating layer is uneven, leading to a problem of cracking, and the average particle size (D) of the second inorganic particle is 50 If ) exceeds 0.70㎛, it means that the particle size is excessively large. In this case, when the electrolyte penetrates into the porous coating layer, it is not evenly distributed internally but aggregates locally, leading to a problem where the expansion rate increases in specific areas and the wet shrinkage rate increases. Additionally, since large particles have difficulty retaining sufficient moisture, the porous coating layer shrinks rapidly upon moisture loss, causing cracks to enlarge. The average particle size (D) of the second inorganic particle mentioned above 50When the above range is satisfied, the BET specific surface area is reduced, which can be advantageous in terms of moisture adsorption and interfacial resistance.

[0059] Meanwhile, the present invention contains more of the first inorganic particles with a small particle size than the second inorganic particles with a large particle size within the porous coating layer. That is, the content of the first inorganic particles within the coating layer is greater than the content of the second inorganic particles. When the content of the second inorganic particles is greater than the content of the first inorganic particles, the wet shrinkage and dry shrinkage increase due to the decrease in substrate adhesion.

[0060] Preferably, the porous coating layer may contain the first inorganic particle and the second inorganic particle in a weight ratio of 55:45 to 95:5, more preferably 60:40 to 85:15, and even more preferably 65:35 to 75:25. When the weight ratio of the first inorganic particle and the second inorganic particle satisfies the above range, the packing density of the porous coating layer increases, and the effect of improving thermal stability is more excellent.

[0061] The first inorganic particle and the second inorganic particle each independently comprise one or more selected from the group consisting of aluminum oxide (Al2O3), boehmite (AlOOH), silicon dioxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), and zeolite, and preferably may comprise aluminum oxide (Al2O3). Such inorganic particles can improve the thermal stability of the separator and prevent the separator from shrinking at high temperatures. Specifically, in the case of aluminum oxide (Al2O3), it has high thermal stability, maintains its shape and properties at high temperatures, and can have a particle shape and size distribution favorable for maintaining a porous structure. It also has an affinity for moisture, allowing it to combine well with the electrolyte and be uniformly dispersed within the coating layer, which ultimately improves the wet shrinkage and dry shrinkage of the separator. On the other hand, if the first inorganic particle or the second inorganic particle contains an inorganic material such as aluminum hydroxide (Al(OH)3) or magnesium hydroxide (Mg(OH)2), the physical properties may change due to easy thermal decomposition or dehydration at high temperatures, which can cause deformation of the porous coating layer. If it contains barium sulfate (BaSO4), it is difficult for the inorganic particles to be uniformly dispersed within the porous coating layer due to hydrophobic properties, and there is a problem of poor compatibility with the binder.

[0062] Meanwhile, the above-mentioned acrylic binder provides adhesion to ensure that the porous coating layer adheres well to the substrate layer, and plays a role in improving the heat resistance, air permeability, and oxidation resistance of the separator.

[0063] As the above acrylic binder, acrylic binders used in the relevant technical field may be used, for example, PAA, PAA-PAM copolymer, PAA-PU copolymer, etc., but are not limited thereto.

[0064] Meanwhile, the acrylic binder may be included in an amount of 1% to 6% by weight, preferably 1% to 4% by weight, and more preferably 1% to 2% by weight, based on the total weight of the porous coating layer. When the above range is satisfied, the resistance can be lowered and the output and capacity increased while maintaining high wet shrinkage, peel strength, and mechanical tensile / puncture strength of the separator.

[0065] Meanwhile, the porous coating layer of the present invention as described above lowers surface resistance and provides conductivity, thereby insulating the cathode and anode, while simultaneously improving the ion mobility of lithium ions and reducing the wet shrinkage and dry shrinkage of the separator.

[0066] The porous coating layer is located on one or both sides of the substrate layer and has a thickness of 1.2 μm to 2.0 μm, preferably 1.4 μm to 1.9 μm, and more preferably 1.6 μm to 1.8 μm. If the thickness of the porous coating layer is less than 1.2 μm, it is difficult to maintain stability in a high-temperature environment due to the thin thickness, and the insulation function cannot be performed, so the synergistic effect of conductivity cannot be obtained. If it exceeds 2.0 μm, the penetration of the electrolyte becomes difficult due to the excessively thick thickness, and since the expansion and contraction occurring when the porous coating layer comes into contact with the electrolyte occur unevenly on the inside and the surface, there is a problem of cracking occurring within the porous coating layer and a problem of battery performance degradation caused by an increase in the movement distance of lithium ions. When the thickness of the porous coating layer satisfies the above range, the performance of the battery can be improved by reducing internal resistance, improving rate characteristics, and reducing the movement distance of lithium ions.

[0067] The porosity of the porous coating layer may be 60% or less, preferably 52% to 60%, and more preferably 54% to 57%. If the porosity exceeds 60%, the effective cohesive bonding surface area becomes smaller, and the mechanical properties of the separator may deteriorate due to weakened adhesion between inorganic materials, thereby potentially worsening electrolyte impregnation and high-efficiency charge / discharge characteristics.

[0068] The loading amount of the above porous coating layer is 4.9 g / cm² 2 Up to 7.0 g / cm² 2 It may be, preferably 5.6 g / cm³ 2 Up to 6.7 g / cm² 2 It may be, and more preferably 6.0 g / cm³ 2 Up to 6.3 g / cm² 2 It is possible. If the above range is satisfied, resistance can be reduced while preventing thermal shrinkage in a high-temperature electrolyte environment.

[0069] The packing density of the above porous coating layer is 1.4 g / cm³ 3 Up to 2.0 g / cm² 3 It may be, preferably 1.6 g / cm³ 3 Up to 1.9 g / cm² 3 It may be, and more preferably 1.7 g / cm³ 3 Up to 1.8 g / cm² 3 It is possible. If the above range is satisfied, resistance can be reduced while preventing thermal shrinkage in a high-temperature electrolyte environment.

[0070] Meanwhile, the porous coating layer can be formed by applying a slurry composition on one or both sides of the substrate layer.

[0071] At this time, the slurry composition can be prepared by adding the first inorganic particles, the second inorganic particles, and the acrylic binder to a solvent. At this time, water, an organic solvent, or a mixture thereof may be used as the solvent, and preferably, water may be used. When water is used as the solvent, a high reaction rate can be obtained due to the effects of high dielectric constant, polarity, and hydrogen bonding.

[0072] Meanwhile, the slurry composition may have a solid content of 20% to 50% by weight, preferably 30% to 40% by weight, and more preferably 33% to 37% by weight. When the solid content of the slurry composition satisfies the above range, appropriate viscosity and particle size distribution for high packing density and coating properties can be secured.

[0074] Lithium secondary battery

[0075] Next, a lithium secondary battery according to the present invention will be described.

[0076] The secondary battery of the present invention comprises a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, wherein the separator used is the separator according to the present invention described above. Since the separator has been described above, the remaining components will be described below.

[0078] (1) positive electrode

[0079] Specifically, the anode according to the present invention may include an anode active material layer comprising an anode active material, and, if necessary, the anode active material layer may further include a conductive material and / or a binder.

[0080] The above-mentioned cathode active material is a compound capable of reversible intercalation and deintercalation of lithium, and may include a lithium transition metal oxide containing lithium and one or more metals selected from cobalt, manganese, nickel, or aluminum; specifically, lithium-manganese-based oxides, lithium iron phosphate, and lithium-nickel-manganese-cobalt-based oxides (e.g., Li(Ni)) which have high capacity characteristics and safety of the battery. p Co q Mn r1 )O2(wherein, 0<p<1, 0<q<1, 0<r1<1, p+q+r1=1) may include at least one.

[0081] Specifically, the lithium-manganese-based oxide may be LiMnO2 or LiMn2O4, and the lithium iron phosphate may be LiFePO4.

[0082] In addition, the above lithium-nickel-manganese-cobalt oxide is Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1 It may include at least one of )O2, and among these, it is preferable to include a lithium transition metal oxide having a nickel content of 60 atm% or more among the transition metals. That is, since higher capacity can be realized as the nickel content among the transition metals increases, using one with a nickel content of 60 atm% or more is more advantageous for realizing high capacity. Such lithium composite metal oxides are Li(Ni 0.6 Mn 0.2 Co 0.2)O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1 At least one selected from the group consisting of )O2 can be cited.

[0083] Meanwhile, in addition to the lithium transition metal oxide, the positive electrode active material of the present invention may include a lithium-cobalt-based oxide (e.g., LiCoO2, etc.), a lithium-nickel-based oxide (e.g., LiNiO2, etc.), and a lithium-nickel-manganese-based oxide (e.g., LiNi 1-Y Mn Y O2(0 <Y<1), LiMn 2-z Ni z O4 (O < Z < 2), lithium-nickel-cobalt oxide (e.g., LiNi 1-Y1 Co Y1 O2(0 <Y1<1), 리튬-망간-코발트계 산화물(예를 들면, LiCo 1-Y2 Mn Y2 O2(0 <Y2<1), LiMn 2-z1 Co z1 O4 (O < Z1 < 2), lithium-nickel-manganese-cobalt oxide (e.g., Li(Ni p1 Co q1 Mn r2 )O4(0<p1<2, 0<q1<2, 0<r2<2, p1+q1+r2=2), or lithium-nickel-cobalt-transition metal (M) oxide (e.g., Li(Ni p2 Co q2 Mn r3 M S2 Examples include )O2(M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg and Mo, and p2, q2, r3 and s2 are each atomic fractions of independent elements, 0<p2<1, 0<q2<1, 0<r3<1, 0<s2<1, p2+q2+r3+s2=1), and any one or more of these compounds may be further included.

[0084] The above positive active material may be included in an amount of 90% to 99% by weight, specifically 93% to 98% by weight, based on the total weight of the solid content in the positive active material layer.

[0085] The above conductive material is not particularly limited as long as it is conductive without causing chemical changes in the battery, and for example, carbon powder such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermal black; graphite powder such as natural graphite, artificial graphite, or graphite with a highly developed crystal structure; conductive fibers such as carbon fibers or metal fibers; conductive powder such as carbon fluoride powder, aluminum powder, or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives may be used.

[0086] The above conductive material is typically added in an amount of 1% to 30% by weight based on the total weight of the solid content in the positive active material layer.

[0087] The above binder is a component that serves to improve adhesion between positive active material particles and the adhesion between the positive active material and the current collector, and is typically added in an amount of 1% to 30% by weight based on the total weight of the solid content in the positive active material layer. Examples of such binders include fluoropolymer-based binders comprising polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); rubber-based binders comprising styrene butadiene rubber (SBR), acrylonitrile-butadiene rubber, or styrene-isoprene rubber; cellulose-based binders comprising carboxyl methyl cellulose (CMC), starch, hydroxypropyl cellulose, or regenerated cellulose; polyalcohol-based binders comprising polyvinyl alcohol; and polyolefin-based binders comprising polyethylene or polypropylene. Examples include polyimide-based binders; polyester-based binders; and silane-based binders.

[0088] The anode of the present invention may be manufactured according to an anode manufacturing method known in the art. For example, the anode may be manufactured by a method of forming an anode active material layer by applying an anode slurry, prepared by dissolving or dispersing an anode active material, a binder, and / or a conductive material in a solvent, onto an anode current collector, and then drying and rolling, or by a method of casting the anode active material layer onto a separate support and then peeling off the support to obtain a film, which is then laminated onto an anode current collector.

[0089] The above positive current collector is not particularly limited as long as it is conductive without causing chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used.

[0090] The above solvent may include an organic solvent such as NMP (N-methyl-2-pyrrolidone) and may be used in an amount that results in a desirable viscosity when the above positive active material and optionally a binder and a conductive material are included. For example, the solid content concentration in the active material slurry containing the positive active material and optionally a binder and a conductive material may be 10% to 70% by weight, preferably 20% to 60% by weight.

[0092] (2) Negative electrode

[0093] Next, the cathode is explained.

[0094] The cathode according to the present invention comprises a cathode active material layer comprising a cathode active material, and the cathode active material layer may further comprise a conductive material and / or a binder as needed.

[0095] The above negative electrode active material may include at least one selected from the group consisting of lithium metal, a carbon material capable of reversibly intercalating / deintercalating lithium ions, a metal or an alloy of these metals and lithium, a metal composite oxide, a material capable of doping and dedoping lithium, and a transition metal oxide.

[0096] As for the carbon material capable of reversibly intercalating / deintercalating the above lithium ions, any carbon-based negative electrode active material commonly used in lithium-ion secondary batteries may be used without particular limitation, and representative examples include crystalline carbon, amorphous carbon, or a combination thereof. Examples of the above crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the above amorphous carbon include soft carbon (low-temperature calcined carbon) or hard carbon, mesophase pitch carbide, calcined coke, etc.

[0097] As the above metal or alloy of these metals and lithium, a metal selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn, or an alloy of these metals and lithium may be used.

[0098] The above metal composite oxides include PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, Li x Fe2O3(0≤x≤1), Li x WO2(0≤x≤1) and Sn x Me 1-x Me y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, Group 1, 2, and 3 elements of the periodic table, halogens; 0 <x≤1; 1≤y≤3; 1≤z≤8) 로 이루어진 군에서 선택되는 것이 사용될 수 있다.

[0099] Materials capable of doping and dedoping the above lithium include Si and SiO x(0 <x<2), Si-Y 합금(상기 Y는 알칼리 금속, 알칼리 토금속, 13족 원소, 14족 원소, 전이금속, 희토류 원소 및 이들의 조합으로 이루어진 군에서 선택되는 원소이며, Si은 아님), Sn, SnO2, Sn-Y(상기 Y는 알칼리 금속, 알칼리 토금속, 13족 원소, 14족 원소, 전이금속, 희토류 원소 및 이들의 조합으로 이루어진 군에서 선택되는 원소이며, Sn은 아님) 등을 들 수 있고, 또한 이들 중 적어도 하나와 SiO2를 혼합하여 사용할 수도 있다. 상기 원소 Y로는 Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po 및 이들의 조합으로 이루어진 군에서 선택될 수 있다.

[0100] Examples of the above transition metal oxides include lithium-containing titanium composite oxide (LTO), vanadium oxide, and lithium vanadium oxide.

[0101] The above-mentioned negative electrode active material may be included in an amount of 80% to 99% by weight based on the total weight of the solid content in the negative electrode active material layer.

[0102] The above conductive material is a component for further improving the conductivity of the negative electrode active material and may be added in an amount of 1 to 20 weight percent based on the total weight of the solid content in the negative electrode active material layer. Such conductive material is not particularly limited as long as it is conductive without causing chemical changes in the battery, and for example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; conductive powders such as carbon fluoride powder, aluminum powder, or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives may be used.

[0103] The above binder is a component that assists in the bonding between the conductive material, the active material, and the current collector, and is typically added in an amount of 1 to 30 weight percent based on the total weight of the solid content in the negative electrode active material layer. Examples of such binders include fluoropolymer-based binders comprising polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); rubber-based binders comprising styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber, or styrene-isoprene rubber; cellulose-based binders comprising carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, or regenerated cellulose; polyalcohol-based binders comprising polyvinyl alcohol; polyolefin-based binders comprising polyethylene or polypropylene; polyimide-based binders; polyester-based binders; and silane-based binders.

[0104] The above-mentioned cathode may be manufactured according to cathode manufacturing methods known in the art. For example, the above-mentioned cathode may be manufactured by applying a cathode active material slurry, prepared by dissolving or dispersing a cathode active material and optionally a binder and a conductive material in a solvent, onto a cathode current collector, rolling, and drying to form a cathode active material layer, or by casting the cathode active material layer onto a separate support and then peeling off the support to obtain a film, which is then laminated onto a cathode current collector.

[0105] The above-mentioned negative current collector generally has a thickness of 3 to 500 μm. Such a negative current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., or aluminum-cadmium alloy may be used. In addition, similar to the positive current collector, fine irregularities may be formed on the surface to strengthen the bonding strength of the negative active material, and it may be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and nonwoven fabrics.

[0106] The above solvent may include water or organic solvents such as NMP or alcohol, and may be used in an amount that results in a desirable viscosity when the above negative electrode active material and optionally a binder and a conductive material are included. For example, the solid content concentration in the active material slurry including the negative electrode active material and optionally a binder and a conductive material may be 50% to 75% by weight, preferably 50% to 65% by weight.

[0108] (3) Electrolyte

[0109] Next, I will explain electrolytes.

[0110] The above electrolyte may include an organic solvent and a lithium salt.

[0111] The above organic solvent may be used without special restrictions as long as it can serve as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the above organic solvent may include ester-based solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether-based solvents such as dibutyl ether or tetrahydrofuran; ketone-based solvents such as cyclohexanone; and aromatic hydrocarbon-based solvents such as benzene and fluorobenzene. Carbonate-based solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC); alcohol-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (where R is a straight-chain, branched, or cyclic hydrocarbon group having C2 to C20 structures and may include a double bond, a directional ring, or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolanes may be used. Among these, a carbonate-based solvent is preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate, etc.) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of the battery, and a low-viscosity linear carbonate-based compound (e.g., ethylmethyl carbonate, dimethyl carbonate or diethyl carbonate, etc.) is more preferred.

[0112] The above lithium salt can be used without special limitations as long as it is a compound capable of providing lithium ions used in lithium secondary batteries. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2, etc. The concentration of the lithium salt is preferably used within the range of 0.1 to 5.0 M, more preferably 0.1 to 3.0 M. When the concentration of the lithium salt falls within the above range, the electrolyte has appropriate conductivity and viscosity, so it can exhibit excellent electrolyte performance and allow lithium ions to move effectively.

[0113] In addition to the electrolyte components, the above electrolyte may further include additives for the purpose of improving the lifespan characteristics of the battery, suppressing the reduction of battery capacity, and improving the discharge capacity of the battery. For example, the above additives may include haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethylphosphite, triethanolamine, cyclic ether, ethylene diamine, n-glyme, hexamethylphosphate triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, either alone or in combination, but are not limited thereto. The above additives may be included in an amount of 0.1 to 10 weight%, preferably 0.1 to 5 weight%, based on the total weight of the electrolyte.

[0114] The present invention will be explained in more detail below through examples. However, the following examples are intended to illustrate the present invention and do not limit the scope of the present invention solely to these examples.

[0116] Examples and Comparative Examples

[0117] Example 1

[0118] Average particle size (D 50 ) first inorganic particle Al2O3 with a diameter of 0.35㎛ and average particle size (D 50 A slurry composition having a solid content of 35% by weight was prepared by adding 30g of inorganic particles, mixed with 0.5㎛ second inorganic particles Al2O3 in a weight ratio of 7:3, and 1.9g of an acrylic binder to water, which is a solvent, and stirring.

[0119] The above slurry composition was coated on both sides of a polyethylene substrate to a thickness of 1.7 μm. At this time, the porous coating layer had a porosity of 53%.

[0121] Comparative Example 1

[0122] Average particle size (D 50 A separation membrane was prepared in the same manner as in Example 1 above, except that only the first inorganic particle with a particle size of 0.35 μm was added.

[0124] Comparative Example 2

[0125] Average particle size (D 50 A first inorganic particle with a diameter of 0.35㎛ and an average particle size (D 50 A separation membrane was prepared in the same manner as in Example 1 above, except that a second inorganic particle with a particle size of 0.5 μm was mixed in a weight ratio of 5:5.

[0127] Comparative Example 3

[0128] Average particle size (D 50 A first inorganic particle with a diameter of 0.35㎛ and an average particle size (D 50 A separation membrane was prepared in the same manner as in Example 1 above, except that a second inorganic particle with a particle size of 0.5 μm was mixed in a weight ratio of 3:7.

[0130] Comparative Example 4

[0131] Average particle size (D 50A separation membrane was prepared in the same manner as in Example 1 above, except that only a second inorganic particle with a particle size of 0.5 μm was added.

[0133] Comparative Example 5

[0134] Average particle size (D 50 A first inorganic particle having a diameter of 0.1㎛ and an average particle size (D 50 A separation membrane was prepared in the same manner as in Example 1 above, except that a second inorganic particle with a particle size of 0.5 μm was mixed in a weight ratio of 7:3.

[0136] Comparative Example 6

[0137] Average particle size (D 50 A first inorganic particle having a diameter of 0.1㎛ and an average particle size (D 50 A separation membrane was prepared in the same manner as in Example 1 above, except that a second inorganic particle with a particle size of 0.8 μm was mixed in a weight ratio of 7:3.

[0139] The average particle size (D) of each of the first inorganic particle and the second inorganic particle used when manufacturing the separation membrane according to Example 1 and Comparative Examples 1 to 6 50 ), average particle size of the first inorganic particle and the second inorganic particle (D 50 The ratio and weight ratio are shown in Table 1 below.

[0141] Average particle size (D 50 )[㎛] Average particle size (D 50 ) rain weight ratio Average particle size of the first inorganic particle (D 50 )[㎛] Average particle size of the second inorganic particle (D 50 )[㎛] Example 1 0.35 0.5 1.42 7:3 Comparative Example 1 0.35 - - 10:0 Comparative Example 2 0.35 0.5 1.42 5:5 Comparative Example 3 0.35 0.5 1.42 3:7 Comparative Example 4 - 0.5 - 0:10 Comparative Example 5 0.1 0.5 5 7:3 Comparative Example 6 0.1 0.8 8 7:3

[0142] Experimental Example 1: Measurement of Wet Shrinkage

[0143] The wet shrinkage of the membranes prepared according to Example 1 and Comparative Examples 1 to 6 was measured in the following manner.

[0144] Each of the above separators was cut into 5cm × 5cm pieces, placed in a 10cm × 9cm pouch with 1g of 1M LiPF6 electrolyte, and then impregnated and stored in a 130℃ convection oven for 30 minutes. Afterward, the separators were separated from the pouch, and the shrinkage rates in the MD and TD directions were measured. The measurement results are shown in Table 2 below.

[0146] Experimental Example 2: Measurement of Dry Shrinkage

[0147] The separators prepared according to Example 1 and Comparative Examples 1 to 6 were each cut into 5 cm × 5 cm pieces, stored in a 150°C convection oven for 30 minutes, removed, and the shrinkage rates in the MD direction and TD direction were measured. The measurement results are shown in Table 2 below.

[0149] Experimental Example 3: Measurement of Loading Amount

[0150] The loading amount of the porous coating layer included in the separators prepared according to Example 1 and Comparative Examples 1 to 6 was calculated by determining the difference in the average weight of each coated separator and base film, cut into 5 cm × 5 cm pieces and measured 6 times respectively. The calculation results are shown in Table 2 below.

[0152] Experimental Example 4: Calculation of Packing Density

[0153] The packing density of the porous coating layer included in the separators prepared according to Example 1 and Comparative Examples 1 to 6 was calculated by dividing the loading amount of the porous coating layer calculated in Experimental Example 3 by 3.4 μm, which is the difference between the total thickness of the separator, 13 μm, and the thickness of the substrate layer of the separator, 9.6 μm. The calculation results are shown in Table 2 below.

[0155] Wet shrinkage [%] Dry shrinkage [%] Loading amount [g / cm 2 ] Packing density [g / cm²] 3 ] MD [%] TD [%] MD [%] TD [%] Example 1 2 1 2 3 6.3 1.85 Comparative Example 1 11 8 69 68 5.0 1.47 Comparative Example 2 8 6 49 42 5.8 1.71 Comparative Example 3 9 7 51 45 5.7 1.68 Comparative Example 4 11 10 56 49 5.4 1.59 Comparative Example 5 11 9 67 65 5.5 1.62 Comparative Example 6 12 10 73 71 5.0 1.47

[0156] Referring to Table 2, it can be seen that the separator according to Example 1 has significantly improved wet shrinkage and dry shrinkage compared to the separators according to Comparative Examples 1 to 6. Accordingly, it can be expected that there will be a significant difference in the heat resistance of the separator when applied to an actual cell.

Claims

Claim 1 A substrate layer; and a porous coating layer located on one or both sides of the substrate layer and comprising a first inorganic particle, a second inorganic particle, and an acrylic binder; wherein the average particle size (D) of the first inorganic particle 50 The average particle size (D) of the second inorganic particle mentioned above for ) 50 A separator having a ratio of ) 1.4 to 1.8, a content of the first inorganic particle greater than the content of the second inorganic particle based on the total weight of the porous coating layer, a thickness of the porous coating layer 1.2㎛ to 2.0㎛, and an MD shrinkage rate of 0.5% to 7.0% and a TD shrinkage rate of 0.5% to 5.5% when the separator is impregnated with an electrolyte and left at 130℃ for 30 minutes. Claim 2 In claim 1, the average particle size (D) of the first inorganic particle 50 ) is a separation membrane with a thickness of 0.32㎛ to 0.5㎛. Claim 3 In claim 1, the average particle size (D) of the second inorganic particle 50 ) is a separator with a thickness of 0.45㎛ to 0.70㎛. Claim 4 A separation membrane according to claim 1, wherein the porous coating layer comprises the first inorganic particle:the second inorganic particle in a weight ratio of 55:45 to 95:

5. Claim 5 A separation membrane according to claim 1, wherein the first inorganic particle and the second inorganic particle each independently comprise one or more selected from the group consisting of aluminum oxide (Al2O3), boehmite (AlOOH), silicon dioxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), and zeolite. Claim 6 In claim 1, the porous coating layer is a separator having a porosity of 60% or less. Claim 7 In claim 1, the loading amount of the porous coating layer is 4.9 g / cm² 2 Up to 7.0 g / cm² 2 A separator that is. Claim 8 In claim 1, the packing density of the porous coating layer is 1.4 g / cm³ 3 Up to 2.0 g / cm² 3 A separator that is. Claim 9 A separation membrane according to claim 1, wherein the porous coating layer is formed by applying a slurry composition having a solid content of 20% to 50% by weight on one or both sides of the substrate layer. Claim 10 A separator according to claim 1, wherein the thickness of the separator is 11㎛ to 14㎛. Claim 11 delete Claim 12 A separator according to claim 1, wherein the MD shrinkage rate is 1% to 50% and the TD shrinkage rate is 2% to 40% when the separator is left at 150°C for 30 minutes. Claim 13 A lithium secondary battery comprising the separator of claim 1.

Citation Information

Patent Citations

  • Composite porous separator, manufacturing method thereof and electrochemical device using the same

    KR1020220137342A

  • Separator and electrochemical device comprising the same

    KR1020230067401A